Clinical case of recurrent parotitis in a child. Discussion of causes - V.V. Mavrutenkov; Z.O. Chykarenko; N.V. Zhukova (Zaslavsky O.Yu., 2018)
Currently, with introduction of vaccination against epidemic parotitis, differential diagnosis of salivary gland involvement in children should include other viruses, such as cytomegalovirus, Coxsackie virus, herpes virus type 6, human T-lymphotropic virus, human immunodeficiency virus, etc., as well as autoimmune and oncologic diseases. Comprehensive differential diagnosis is required before establishing the diagnosis of exclusion, such as juvenile recurrent parotitis. It will ensure more effective therapeutic approach and avoiding the prescription of unnecessary medicines and manipulations. The article presents detailed clinical case of recurrent parotitis in a fully vaccinated (according to national vaccination schedule) 6-year-old boy, who experienced several episodes of painless swelling of the left parotid area without fever or with low-grade fever accompanied by redness in the left eye during observation. Performed laboratory survey and instrumental examination are given. Methods and efficacy of therapeutic approach are described. The article presents etiological classification of salivary gland involvement, which includes inflammatory diseases, autoimmune and hypertrophic lesions, obstructive and traumatic conditions, developmental defects, tumors. Epidemiologic and etiologic features of parotitis in pediatric population are considered. Differential diagnosis also includes, for example, Sjogren's syndrome, sarcoidosis, cat-scratch disease, Parinaud conjunctivitis, with description of diagnostic criteria of the mentioned conditions. According to clinicians, juvenile recurrent parotitis was diagnosed in the presented case. The article presents epidemiological features of this pathology, diagnostic criteria, discussion of possible etiology, recommendations for the management. Necessity and safety of vaccination against epidemic parotitis were accentuated, as well as importance of avoiding the prescription of unnecessary medicines. Vaccination against epidemic parotitis is a prerequisite for the prevention of viral lesions of the salivary glands. It also helps to narrow the differential diagnosis of parotitis causes. If diagnosis of epidemic parotitis is excluded in a child, comprehensive clinical, laboratory and instrumental examination is recommended. It is very important to provide follow-up after the first episode of parotitis in order to exclude recurrent course of the disease. In the presence of recurrent parotitis and exclusion of other causes of damage to the parotid salivary gland, it should be suggested that the child has juvenile recurrent parotitis, which is a diagnosis of exclusion, and can be made after at least 12 months of follow-up. The drug management of juvenile recurrent parotitis should exclude unreasonable prescription of medicines, such as antibiotics, antiviral drugs and especially immunomodulators. Only symptomatic therapy is indicated, providing relief of symptoms. Systematic follow-up of patients with this pathology is required.